The Role of Multimodality Imaging in HIV-Associated Cardiomyopathy - Gambahaya, Ellise T.; Rana, Rimsha; Bagchi, Shashwatee; Sharma, Garima; Sarkar, Sudipa; Goerlich, Erin; Cupido, Blanche; Mukherjee, Monica; Hays, Allison G. (Frontiers in Cardiovascular Medicine, 2022)
Despite marked advances in therapeutics, HIV infection remains a leading cause of morbidity and mortality worldwide. HIV infection is associated with cardiovascular complications including myocardial and vascular dysfunction. The description of HIV-associated cardiomyopathy (HIVAC) has evolved over time from a predominantly dilated cardiomyopathy with systolic dysfunction to one of subclinical diastolic dysfunction. Multimodality cardiovascular imaging plays an integral role in our understanding of the etiology and pathogenesis of HIVAC. Cardiovascular imaging is also essential in the evaluation of individuals with chronic HIV disease who may have subclinical atherosclerosis and myocardial dysfunction. In the present review, we will highlight current evidence for the role of multimodality cardiovascular imaging in establishing the diagnosis, etiology and pathophysiology of HIVAC as well as guiding treatment and assessing prognosis.